Implementation of Information Technology in Increasing the Efficiency and Effectiveness of MSME Business Processes - Ming Pong; Teddy Oswari; Fatimah Fahurian; Triyugo Winarko (Yayasan Adra Karima Hubbi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving economic growth, particularly in emerging economies. However, MSMEs often face challenges related to limited resources, outdated business processes, and inefficient operational practices. The implementation of information technology (IT) has emerged as a potential solution to improve business processes, streamline operations, and enhance competitiveness. This study aims to examine the impact of information technology implementation on the efficiency and effectiveness of business processes in MSMEs. The research seeks to identify key factors that influence the adoption of IT, as well as assess how it contributes to improving operational efficiency, decision-making, and overall business performance in MSMEs. The findings revealed that MSMEs that integrated IT solutions experienced notable improvements in process efficiency, reduced operational costs, and enhanced decision-making. Over 70% of surveyed businesses reported better inventory management and faster response times to customer needs. Moreover, businesses leveraging IT tools showed a significant increase in productivity and profitability. The implementation of information technology significantly enhances the efficiency and effectiveness of MSME business processes.